Antimigraine Drug Avitriptan Is a Ligand and Agonist of Human Aryl Hydrocarbon Receptor That Induces CYP1A1 in Hepatic and Intestinal Cells - Vyhlídalová, Barbora; Krasulová, Kristýna; Pečinková, Petra; Poulíková, Karolína; Vrzal, Radim; Andrysík, Zdeněk; Chandran, Aneesh; Mani, Sridhar; Dvorak, Zdenek (International journal of molecular sciences, 2020)
The efforts for therapeutic targeting of the aryl hydrocarbon receptor (AhR) have emerged in recent years. We investigated the effects of available antimigraine triptan drugs, having an indole core in their structure, on AhR signaling in human hepatic and intestinal cells. Activation of AhR in reporter gene assays was observed for Avitriptan and to a lesser extent for Donitriptan, while other triptans were very weak or no activators of AhR. Using competitive binding assay and by homology docking, we identified Avitriptan as a low-affinity ligand of AhR. Avitriptan triggered nuclear translocation of AhR and increased binding of AhR in CYP1A1 promotor DNA, as revealed by immune-fluorescence microscopy and chromatin immune-precipitation assay, respectively. Strong induction of CYP1A1 mRNA was achieved by Avitriptan in wild type but not in AhR-knockout, immortalized human hepatocytes, implying that induction of CYP1A1 is AhR-dependent. Increased levels of CYP1A1 mRNA by Avitriptan were observed in human colon carcinoma cells LS180 but not in primary cultures of human hepatocytes. Collectively, we show that Avitriptan is a weak ligand and activator of human AhR, which induces the expression of CYP1A1 in a cell-type specific manner. Our data warrant the potential off-label therapeutic application of Avitriptan as an AhR-agonist drug.
Keywords: hepatocyty; Basic Helix-Loop-Helix Transcription Factors; aktivace enzymů; Intestinal Mucosa; orgánová specificita; repurposing; Aryl Hydrocarbon Receptor; Enzyme Activation; Up-Regulation; simulace molekulového dockingu; transkripční faktory bHLH; tryptaminy; lidé; receptory aromatických uhlovodíků; Sulfonamides; upregulace; kultivované buňky; Cytochrome P-450 CYP1A1; Tryptamines; Hepatocytes; Ligands; Models, Molecular; Cells, Cultured; Receptors, Aryl Hydrocarbon; molekulární modely; sulfonamidy; Drug Repositioning; cytochrom P-450 CYP1A1; Organ Specificity; Triptans; Antimigraine drugs; promotorové oblasti (genetika); Promoter Regions, Genetic; přehodnocení terapeutických indikací léčivého přípravku; Molecular Docking Simulation; ligandy; střevní sliznice; Humans